Augmenting the performance of pyramid distiller via conical absorbing surface, reflectors, condenser, and thermal storing material. (25th November 2022) - Essa, Fadl A.; Alawee, Wissam H.; Abdullah, A.S.; Aljaghtham, Mutabe; Mohammed, Suha A.; Dhahad, Hayder A.; Majdi, Ali; Omara, Z.M.
Abstract: The availability of freshwater suitable for human use is a modern problem in many countries of the world. There are different methods that can be considered to overcome this problem, among them solar distillers, which are an acceptable solution in places far from urbanization and for families of medium numbers. This paper presents a different design of the pyramid distiller (PSS). This was conducted by changing the flat absorber to a conical absorber to increase the vaporization surface area of distiller. In addition, various wick materials of cotton wick and jute cloth were placed over the conical absorber to be investigated. Besides, the performance of the modified pyramid solar still (MPSS) was studied when using external mirrors to increase the input solar energy and utilizing external condenser. Finally, a paraffin wax mixed with silver nanoparticles was used as a phase change material (PCM) under the conical absorber of MPSS to be tested. The results revealed that using the modified conical absorber increased the evaporative surface area of MPSS by around 14 %. Also, using the jute cloth material is suggested to be used instead of cotton cloth as a wick material for the MPSS due to its better operation, where the distillate of MPSS with cotton and jute wicks was increased by 66 % and 69 % over that of the PSS. While the daily yield of the MPSS with reflectors and external condenser was reported as 10, 250 mL/m 2 ·day compared to only 3950 mL/m 2 ·day for the PSS. As a result, the combination of mirrors and external condenser with the MPSS improved the yield by 159 % over that of the PSS. Finally, the best performance of MPSS was obtained under the conditions of using mirrors and condenser, where the daily yield improvement and distiller efficiency were 159 % and 55.5 %, respectively. Highlights: The flat absorber of a pyramid solar still is changed to a conical absorber. Various wicks with condenser, mirrors and PCM are tested. Best still performance was achieved when utilizing condenser and mirrors. Thermal efficiency and productivity rise reached 55.5 % and 155 % respectively